STRATEGI PENGEMBANGAN POTENSI WISATA RELIGIUS BUKIT KASIH TOAR LUMIMUUT KANONANG KABUPATEN MINAHASA - WALANGITAN, OLIVIA CHRISTINE (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract: a reliable regional tourism industry should have a marketing concept in the form ofmanagement applied to seize the tourism market. The purpose of this study was to determine how thestrategy of development of religious tourism potential Hill Love Toar Lumimuut Kanonang ".This study uses survey research aims to examine all the elements involved in the management anddevelopment of the Mount of Love. Location done in the village Kanonang, namely the attraction ofreligion "Hill Love Toar Lumimuut". For the primary source of data, the number of respondents wastaken 100 500 visitors and 50 100 merchants.The results showed Hill Love Kanonang should be able to optimize the potential or become competitiveadvantages and capabilities Hill Love Kanonang management should be encouraged and become better.Keywords: Development of Tourism Potential